PENERAPAN GREEN ECONOMY DALAM PENGEMBANGAN DESA EKOWISATA MANGROVE LEMBUNG UNTUK MEWUJUDKAN WAWASAN LINGKUNGAN - Sufiyanto, Mohamamd Imam; Khairunisa, Khairunisa; Nasrullah, Achmad Muzammil Alfan; Kusumawati, Hesti; Yasin, Roychan (STIE Pelita Nusantara, 2025)
Ecotourism is a form of sustainable tourism that not only focuses on environmental conservation but also on improving the welfare of local communities. Community empowerment in the management and utilization of ecotourism is an important aspect of creating active involvement and ownership of natural resources. This research aims to examine the role and strategy of community empowerment in participatory-based ecotourism development. The method used is a qualitative approach with data collection techniques through interviews, observations, and documentation studies in local communities in ecotourism areas. The results of the study show that community participation in ecotourism can increase economic capacity, strengthen local cultural values, and create a sense of responsibility for environmental conservation. However, challenges such as limited access to information, low managerial capacity, and lack of policy support remain obstacles that need to be overcome. Therefore, a collaboration between the government, non-governmental organizations, and the private sector is needed to strengthen the position of the community as the main actor in sustainable ecotourism management. Keywords : community empowerment, ecotourism, participation, environmental conservation, sustainable development.